Diversity of Social Wasps on Semideciduous Seasonal Forest Fragments with Different Surrounding Matrix in Brazil - Getulio Minoru Tanaka Junior; Fernando Barbosa Noll (Psyche: A Journal of Entomology)
We surveyed social wasps (Polistinae) present in forest fragments of northwest of São Paulo state with different surroundings composed of a matrix of citrus crops and sugarcane in the expectation that the former matrix would be more diverse than the latter. We collected specimens actively using attractive liquids. We obtained 20 species in Magda, 13 in Bebedouro, 13 in Matão, and 19 in Barretos. The most common genus was Agelaia in all of the areas. The greatest Shannon-Wiener index of diversity was obtained in Magda (H′=2.12). Species such as Brachygastra moebiana, Metapolybia docilis, Mischocyttarus ignotus, M. paulistanus and M. consimilis had not been recorded on recent surveys in the state. Furthermore M. consimilis is a new record for the state. We concluded that, with our data, a relation between the occurrence of social wasps and the surrounding matrix was not detected.